SLEEP CYCLES AND SPORTS: ANALYZING SEASONAL SLEEP TRENDS AMONG COLLEGE STUDENT ATHLETES - Warner, Sarah Elizabeth; Robertson, Michael James (International Research Journal Diagnostics, 2024)
Sleep, a reversible state of perceptual disengagement from the environment, is a fundamental aspect of human health and performance. It comprises two distinct stages: rapid eye movement (REM) and non-REM (NREM) sleep, each characterized by unique physiological and neurological features. The National Sleep Foundation recommends 7 to 9 hours of sleep for young adults and adults, yet studies reveal that college athletes often fall short of these guidelines, averaging approximately 6.8 hours per night. These sleep deficits are further compounded by daytime fatigue reported by 61% of NCAA athletes. Furthermore, the preference for more sleep is evident among both male and female athletes, with 70% and 82%, respectively, expressing a desire for increased rest. Sleep inconsistency is prevalent among young adults due to late-night activities and strict morning schedules, contributing to the complex issue of sleep deprivation in college athletes. This abstract highlights the substantial impact of sleep insufficiency on the well-being and performance of this population.